Simulasi Monte Carlo untuk Memprediksi Persediaan Darah - Rahmi Darnis; Gunadi Widi Nurcahyo; Yuhandri Yunus (SEULANGA SYSTEM PUBLISHER, 2020)
Blood is a special organ as a communication and transportation system whose job is to circulate nutrients and oxygen. As a very vital transport system and its very useful existence for many people, blood must be managed properly. Monte Carlo simulations can predict problems related to blood stock and demand for blood. The data that is processed to predict blood supply is blood production data in 2018 and 2019, Simulation results data for 2018 are compared with real data for 2019 and simulation results for 2019 are compared with real data for 2020. The results of the simulations that have been carried out have an accuracy rate of 96.21% for 2018 and 79.22% for 2019. Based on the results of the tests that have been done, it can provide information that can help in the management of forecasting future blood stocks.